(3MGTjI Ydi GdahGFO GdVjGFjI TQM GdcGajI ddLGejs - (3GdCSaQGjjfj, GdYUGe, EHQGgje Hf eMeO Hf YQH TGg, J(B945(3g`s
(3ChdgG (B:s
(3fGbU GdChd, hChdg(B: (3deG CejJ Ydi faSc hdG jNai Cf gPG GdMeO CYdi hCMd aj CaQGO hGdMeO hdgPG GNJGQg fHjfG Udi Gddg Ydjg hSde djdI GdeYQGLs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3HGdTYQ hCdMb MQcI GdSQGH hGUWQf hGdbGJe GdZjGH GdeQJaY hGdCYeGb LeY Yeb HGdaJM hbO jVes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 66s
(3eYLe GdeDdajf(B: 1 / 67s
(3cTa GdXfhf(B: 2 / 1372s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs